The Relationship Between Diagnosis Of Acute Appendicitis And Leukocytosis Laboratory Results In The General Hospital Of Muhammadiyah Malang Period 2016-2017 - Mochamad Aleq Sander (Saintika Medika, 2020)
In making the diagnosis in patients with symptoms that are not typical, the doctor needs to do a supporting examination, one of which is an examination of leukocytes count. This examination is very supportive for the diagnosis of acute appendicitis, can be done at the public health center, the price is affordable, and simple. The number of leukocytes in acute appendicitis generally increases to around 10,000-18,000 µL. The experience at UMM General Hospital also varies greatly in the number of leukocytes in patients with acute appendicitis. We often encounter patients with acute appendicitis who have increased leukocytes (leukocytosis), but it is not uncommon to see patients with normal leukocytes. This type of research was analytic observational with cross-sectional. Samples are all patients with a diagnosis of acute appendicitis that fulfills the criteria of inclusion in inpatient installation of UMM General Hospital. Free variables: leukocytosis and dependent variable: acute appendicitis. Data was analyzed using categorical comparative table 2x2 chi square, with confidence interval of 95% using SPSS release 20. The results showed a significant correlation between appendicitis and leukocytosis with sig = 0.000. The conclusion shows that there is a relationship between the diagnosis of acute appendicitis and the results of leukocytosis laboratory at UMM General Hospital Malang.